Adaptability of Bos taurus Cattle Under Hot Arid Conditions - M.Marshal, I Fayez; M.Habeeb, A Alnaimy (Annals of Arid Zone, 2016)
Climatic heat is the major constraint on Bos taurus cattle production in hot arid zones due to the drastic changes that occur in their biological functions. Appetite, feed intake, feed efficiency and feed utilization are impaired. At the same time, disturbances in metabolism of water, protein, energy and minerals occur. Similar disturbances occur in enzymatic reactions and hormonal secretions. Such disturbances lead to depression in some of the blood metabolites. The final result of all these changes is the impairment of growth, milk yield and reproduction. The possible mechanisms of these changes are reviewed.